Performance of monolithic and dry joints with GFRP bolts reinforced with different fibres and GFRP bars under impact loading - Ngo, Tang Tuan; Pham, Thong; Hao, Hong; Chen, Wensu; Elchalakani, M. (ELSEVIER SCI LTD, 2021)
This study investigates the performance of monolithic and newly proposed dry beam-column joints using GFRP bolts, GFRP reinforcements, and different types of fibres subjected to pendulum impact. Six specimens were cast and tested with increasing impact velocity until failure. The experimental results have shown that the proposed concrete dry joint reinforced with fibres and GFRP bars showed better behaviour in terms of energy dissipation (up to 51%), reduced damage level, and reduced maximum and residual displacement as compared to the monolithic joint with GFRP reinforcements. The test results suggested that steel bolts and steel reinforcements could be effectively replaced by GFRP bolts and GFRP reinforcements to mitigate the corrosion problem while still satisfy the design requirements for beam-column joints in both strength and ductility. Furthermore, the use of steel fibres (StFs) demonstrated impressive performance in the critical indices such as damage level and displacement at high impact energies, compared to synthetic fibres (SyFs). Meanwhile, the application of SyFs led to greater energy dissipation than that of StFs (between 6 and 30%). The proposed dry joints could be potentially applied in practice to reduce the construction costs and the damaged/deteriorated components would be easily replaced.